Antimicrobial Effects of Black Tea (Camellia sinensis) on Pseudomonas Aeruginosa Isolated from Eye Infection - Flayyih, May; Yousif, Hanaa; Subhi, Israa (Iraqi Journal of Science, 2024)
This study was conducted to evaluate the effects of black tea on Pseudomonasaeruginosa isolated from eye infection. One hundred samples (corneal scrapings)were obtained. Approximately, 77% of the cases were due to contact lens wearfollowed by 15 % trauma and 8% with unknown history. The isolates identified asP. aeruginosa were 30% (23/77 CL) and 25% (2/8 Unknown). On the other hand,the Kirby-Bauer antibiotic sensitivity assay showed that 100% of the isolates weresensitive to Neomycin, Gentamicin and Amikacin. While 91.6% were sensitive toCarbenicillin and Ceftriaxone; 66.6% were sensitive to Cefotaxime and 0% weresensitive to Tertacycline. Only two isolates were found to be multidrug resistant.Screening for some Pseudomonas virulence factors such as hemolysin and proteaseshowed that all the isolates had the ability to produce Beta hemolysin and digestedcasein due to protease secretion. For adhesion ability using Christensen’s method,8.33% were recorded as strong (+++), 41.66% were moderate (++) while 50% wereweak (+).In contrast black tea (Camellia sinensis) was examined for itsantimicrobial activity. The agar-well diffusion method was used for theconcentrations 100, 200, 300, and 400mg/ml respectively. Results showed that theminimum inhibitory concentration of tea alcohol extract was 400mg/ml withinhibition zone of 20mm. The extract decreased the bacterial viable count since itshowed a visible decrease to <5×10P6P Colony Forming Unite (CFU)/ml after 24 hoursof incubation. Black tea extract also had the ability to completely inhibitPseudomonas growth on blood agar and inhibited protease activity and adhesion.There were also differences in Congo red binding seen in bacterial cell suspensionscultured in growth media that contained tea extract. The synergistic activity of teaextract with antibiotics has changed the resistance of P. aeruginosa (without the tea)to sensitive (in presence of tea extract).